POLICY INNOVATION OF 'JEMPUT SAKIT ANTAR SEHAT' AS HEALTH ACCESSIBILITY IN MAGELANG CITY - Diah, Diah Utami Lutfiana; Gerry, Gerry Katon Mahendra (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Access issues often become a barrier to getting excellent health services due to geographical, economic, and health limitations. To overcome this, the Magelang City Government, through the Public Safety Center (PSC), launched the innovative Jemput Sakit Antar Sehat (JSAS) service. This service is available 24 hours a day and can be used in emergency and non-emergency situations free of charge. This study used a qualitative descriptive method, with data obtained through observation, interviews, and documentation. The results showed that JSAS is very useful, especially for people who do not have access to medical transportation. This service is also considered superior to the previous system due to its flexibility and broader reach. However, several challenges are still faced, such as the limited number of medical personnel and vehicles, and the lack of socialization, which causes minimal public knowledge about this service. To increase the effectiveness of JSAS, additional human resources and fleets are needed, such as increased socialization through the media and community leaders, and collaboration with the private sector or social institutions to support the sustainability of the program.